The climate of war: violence, warfare, and climatic reductionism. (28th July 2015) - Livingstone, David N.
Abstract: National security agencies and other interested parties now often regard conflict as the inevitable consequence of climate change. This inclination to reduce war to the vicissitudes of climate is not new however. Here, I examine some of the earlier ways in which violence was attributed to climatic conditions, particularly in the United States, and trace links between these older advocates of climatic determinism and the recent writings of those insisting that climate change will usher in a grim world of chronic warfare. It ends by drawing attention to the writings of some critics who are troubled by the ease with which climatic reductionism is capturing the public imagination. WIREs Clim Change 2015, 6:437–444. doi: 10.1002/wcc.352 This article is categorized under: Climate, History, Society, Culture > Ideas and Knowledge